2018
DOI: 10.3389/fnagi.2018.00214
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Related Perfusion Pattern Measured With Arterial Spin Labeling MRI in Healthy Subjects

Abstract: Aim: To analyze age-related cerebral blood flow (CBF) using arterial spin labeling (ASL) MRI in healthy subjects with multivariate principal component analysis (PCA).Methods: 50 healthy subjects (mean age 45.8 ± 18.5 years, range 21–85) had 3D structural MRI and pseudo-continuous ASL MRI at resting state. The relationship between CBF and age was examined with voxel-based univariate analysis using multiple regression and two-sample t-test (median age 41.8 years as a cut-off). An age-related CBF pattern was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
44
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 64 publications
14
44
4
Order By: Relevance
“…The observed average, gender and age effects were consistent with previous reports. The age effects on CBF values were in agreement with previous reports (Chen et al, 2011;Zhang et al, 2018), with decreases mainly found in regions that are associated with high perfusion and metabolic demand, including precuneus, cuneus, prefrontal cortices and cerebellum. We also observed age-related increase in CBF in temporal regions, which may reflect macro-vascular artifacts that are common to arterial spin labelling findings (Detre et al, 2012;Mutsaerts et al, 2017) due to prolonged arterial transit time with ageing (Dai et al, 2017).…”
Section: Neurovascular Signals and Age-differences In Rsfasupporting
confidence: 92%
“…The observed average, gender and age effects were consistent with previous reports. The age effects on CBF values were in agreement with previous reports (Chen et al, 2011;Zhang et al, 2018), with decreases mainly found in regions that are associated with high perfusion and metabolic demand, including precuneus, cuneus, prefrontal cortices and cerebellum. We also observed age-related increase in CBF in temporal regions, which may reflect macro-vascular artifacts that are common to arterial spin labelling findings (Detre et al, 2012;Mutsaerts et al, 2017) due to prolonged arterial transit time with ageing (Dai et al, 2017).…”
Section: Neurovascular Signals and Age-differences In Rsfasupporting
confidence: 92%
“…The magnitudes of the observed CBF decreases in our study were larger than age-related CBF changes reported in the literature. For example, the percentage change in mean global GM CBF in this study is about −4.8% per year, more than 10 times larger than reported age-related changes, which range from −0.38 to −0.45% per year ( Biagi et al, 2007 , Parkes et al, 2004 , Wagner et al, 2012 , Zhang et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 70%
“…Since we found significant correlations between PDRP z-scores and age in healthy controls, it could be suggested that ageing and PD share certain metabolic features. Metabolic decreases have been reported in the parietal cortex in normal aging [47,48]. This may cause some overlap with the PDRP.…”
Section: Discussionmentioning
confidence: 93%